Analisis Efektivitas Penerapan Maintenance pada Mesin Produksi Furniture (Rustic) Studi Kasus di PT. Rajawali Perkasa Furniture - Ratri Rahmawati; Sigit Arrohman; Rianto Wibowo; Bella Chintya Reira Christata; Heni Risnawati; Tuti Nadhifah (LPPM Politeknik Jambi, 2026)
Rustic wood refers to a type of wood that has a rough, natural appearance, and often retains the original characteristics of the wood. The term